GAYA KEPEMIMPINAN KEPALA MADRASAH TSANAWIYAH YAYASAN MIFTAHUL HUDA DESA JAYA BAKTI KECAMATAN ENOK KABUPATEN INDRAGIRI HILIR - M. Aulia Qodri; Nur Komariah; Maimunah Maimunah (CV. ADIBA AISHA AMIRA, 2023)
This study aims to describe and analyze the leadership style used by the head of the madrasah tsanawiyah, the Miftahul Huda Foundation, Jaya Bakti Village, Enok sub-district, Indragiri Hilir district. This study uses a descriptive qualitative approach with a case study research design. The research was held on September 9 2022 to December 9 2022 at the Madrasah Tsanawiyah Miftahul Huda Foundation Miftahul Huda Jaya Bakti Village, Enok District, Indragiri Downstream District. The techniques in data collection used were non-participant open observation, semi-structured interviews and documentation studies. Techniques for analyzing data use credibility, transferability, depenability and confirmability. The results of this study can be explained: the dominant leadership style used by the head of the madrasah tsanawiyah Miftahul Huda is the Democratic leadership style because the head of the madrasa cooperates with subordinates to achieve common goals, in making decisions the head of the madrasa holds deliberations and consensus, and also the head of the madrasa respects opinion, and consider every opinion from the madrasa operator. Besides that, the head of the madrasa also uses the Ohio leadership style, it can be seen that the head of the madrasa has a gentle attitude towards operators and teachers and directs operators and teachers well. This makes the leadership style applied by the head of the Madrasah Tsanawiyah Miftahul Huda work well. The conclusion of this study is that the leadership style used by the head of the Madrasah Tsanawiyah Foundation Miftahul Huda Indaragiri Hilir is dominant democratic, it can be seen that the head of the madrasa in making decisions with the head of the madrasa always holds deliberations. gentle.